Existence of Bounded Solutions for Sylvester Matrix Dynamical Systems on Time Scales (International Journal of Food and Nutritional Sciences, 2021)
In this paper, the existence criteria for bounded solutions of Sylvester matrix dynamical systems on time scales are studied. The advantage of studying this system is that it unifies continuous and discrete systems. Sylvester matrix dynamical systems on time scales are considered, and for every Lebesgue-delta integrable function F on time scale T+, an investigation is carried out.